The Unprecedented Epidemic of Covid-19 and Movement Control Order (MCO) Enforcement: Impact and Recovery Towards Child Care Services Industry in Malaysia - et.al, Aidanazima Abashah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper aims to examine the impact of the Covid-19 MCO on child care performance and the recovery strategies to be implemented for post-MCO outbreaks. The quantitative approach is used to investigate the impact of the Covid-19 MCO and to plan recovery strategies based on the questionnaire survey conducted by the child care provider. The paper discusses the provider of child care in Malaysia and shows that Covid-19 Movement Control Order (MCO) affects most child care operations in terms of their cash flow and performance. This study represented only child care providers in Malaysia's northern states who are willing to participate. Consequently, the research suggested that the holistic area in Malaysia should be covered. Extensive research is thus warranted. Child care providers should consider the recovery planning strategy for their business survival due to MCO enforcement. The paper examines the global issues of Covid-19 that lead to a partial lockdown or Movement Control Order (MCO) where the business operation is indirectly adversely affected, especially in the child care industry scenario in Malaysia